アイスコアサンプル ヲ タイショウ トシタ ケイコウ ケンビキョウ ニヨル ビセイブツ テイリョウ ホウホウ ノ ケントウ - 植竹, 淳; ウエタケ, ジュン; 東, 久美子; アズマ, クミコ; 本山, 秀明; モトヤマ, ヒデアキ; Uetake, Jun; Goto-Azuma, Kumiko; Motoyama, Hideaki (2012)
P(論文) 氷床アイスコア中には,鉱物粒子と共に輸送されてきた微生物が含まれる事が知られている.これら微生物の細胞数の計測には,蛍光顕微鏡による直接観察法が用いられるが,細胞数が少ないアイスコア試料では蛍光染色試薬の退色により数を過小評価しやすい一方で,含まれる鉱物などの非特異的な蛍光により過大評価しやすいため,定量的に細胞数を測定する事が困難である.本研究では5種の退色防止試薬から退色が最も少ないもの,19種の蛍光染色試薬から非特異的蛍光との選別が容易な試薬をそれぞれ選出し,細胞壁構造の異なる6種の微生物株を用いて染色選択性を確認し,鉱物の混入による染色への影響を調べた.その結果,退色防止試薬にはEverBrite Mounting Medium(Biotium製),蛍光染色試薬にはYOYO-1(Molecular Probes)が最も適していることがわかり,鉱物が混入する場合は濃度をやや高めに調整することで定量性が高くなる事が示された. Ice cores recovered from ice sheets contain microorganisms that were transported to the surface of the ice sheet along with airborne dust. The abundance of microorganisms in ice cores, as measured by direct cell count under a fluorescence microscope, is generally lower than that in other aquatic environments. It is possible that the abundance of microorganisms in ice cores is underestimated due to the degradation of fluorescent dye or because non-specific fluorescence from mineral particles inhibits the fluorescence signal from microorganisms. To investigate this possibility, we tested 4 types of antifade solution and 19 types of fluorescence dye, and selected the best combination in terms of prolonging the fluorescent signal from microorganisms and distinguishing biological signals from noise produced by non-specific particles. The results show that the optimal combination of solution and dye for cell counts of scarce microorganisms in ice cores is the nuclear acid dye ＂YOYO-1＂ (Molecular Probes) and the antifade solution ＂EverBrite Mounting Medium＂ (Biotium). departmental bulletin paper